Investigation of the Crystallographic Perfection and Photoluminescence Spectrum of the Epitaxial Films of (Si2)1-x(GaP)x0≤x≤1 Solid Solution, Grown on Si and GaP Substrates with the Crystallographic Orientation (111) - A. S. Saidov; D. V. Saparov; Sh.N. Usmonov; A. Kutlimratov; J.M. Abdiev; M. Kalanov; A.Sh. Razzakov; A.M. Akhmedov (Advances in Condensed Matter Physics)
Epitaxial layers of the solid solution of molecular substitution (Si2)1-x(GaP)x (0 ≤ x ≤ 1) on Si (111) and GaP (111) substrates are grown by liquid-phase epitaxy from an Sn solution-melt. Such graded-gap solid solutions allow the integration of well-established silicon technology with the advantages of III-V semiconductor compounds. The structural features, the distribution of the atoms of the components over the thickness of the epitaxial layer, the photoluminescence spectrum of the (Si2)1-x(GaP)x (0 ≤ x ≤ 1) solid solution, and the electroluminescence of the structure n-GaP-n+-(Si2)x (GaP)1-x (0 ≤ x ≤ 0.01) have been investigated. It is shown that the layers of the solid solution have a perfect single-crystal structure with the crystallographic orientation (111), with the size of subcrystallites ∼ 39 ± 1 nm. The epitaxial layer (Si2)1-x(GaP)x (0 ≤ x ≤ 1) is a graded-gap layer with a smoothly and monotonically varying composition from silicon to 100% GaP. The energy levels of atoms of Si2 molecules which are located 1.47 eV below the bottom of the conduction band of gallium phosphide are revealed. Red emission of n-GaP-n+-(Si2)x(GaP)1-x (0 ≤ x ≤ 0.01) structure which is caused by electron transitions with participation of energy levels of Si2 atoms is detected.